(untitled) - Bentley, Jerry H. (New York, 2011)
Traditions & Encounters" also has a rich history of firsts: the first world history text to take a truly global perspective on the past; the first to emphasize connections among cultures; and, the first to combine twin themes with a seven-part framework, making the huge story of world history more manageable to both teach and learn.
Keywords: World history,Intercultural communication,Lịch sử thế giới,Giao tiếp liên văn hóa